Conflicto adolescente e inclusión social en jóvenes con discapacidad. Un aporte desde el Psicoanálisis - Péres de Plá, Esperanza (2006)
The author bases on her experience as a psychotherapist of disabled adolescents propose that for Parents, educators and specialists, adolescence is a phase that is used to denied, omitted, postponing The process even more. Through the commentary of case, we specify how the process of the Adolescence is also a second possibility of rebuilding psychic structure for the disabled youngster.